2014
DOI: 10.1093/bib/bbu010
|View full text |Cite
|
Sign up to set email alerts
|

Toward more realistic drug-target interaction predictions

Abstract: A number of supervised machine learning models have recently been introduced for the prediction of drug–target interactions based on chemical structure and genomic sequence information. Although these models could offer improved means for many network pharmacology applications, such as repositioning of drugs for new therapeutic uses, the prediction models are often being constructed and evaluated under overly simplified settings that do not reflect the real-life problem in practical applications. Using quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
459
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(491 citation statements)
references
References 48 publications
10
459
1
Order By: Relevance
“…In contrast, Kinase contains continuous values of binding affinity for drugtarget pairs. In order to produce a binary interaction matrix, we used the same cutoff threshold as Pahikkala et al [37]. Drug-to-drug similarities were computed based on the chemical structure of the compound via the SIMCOMP algorithm (GPCR, IC, NR and E datasets) or via the 2D Tanimoto coefficients (Kinase dataset).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Kinase contains continuous values of binding affinity for drugtarget pairs. In order to produce a binary interaction matrix, we used the same cutoff threshold as Pahikkala et al [37]. Drug-to-drug similarities were computed based on the chemical structure of the compound via the SIMCOMP algorithm (GPCR, IC, NR and E datasets) or via the 2D Tanimoto coefficients (Kinase dataset).…”
Section: Methodsmentioning
confidence: 99%
“…In light of previous works highlighting the perils of cross-validation using paired data [6,7], we recently investigated the effect of using drug-wise disjoint cross-validation in predicting drug-disease pairs, where none of the drugs in the training set appeared in the test set [8]. We showed that the prediction accuracy of the classifier drops dramatically under such cross-validation setting, suggesting that the existing approaches are prone to over-fitting due to the inherent relationships in the data.…”
Section: Bodymentioning
confidence: 96%
“…The proposed models are typically benchmarked using cross-validation, in which the known drug-disease or drug-drug associations are split into training and test sets. Though these methods report areas under receiver operating characteristic (ROC) curves around 90% under cross-validation, their applicability in translational medicine and, thus, ability to reduce drug development costs has been controversial [2,4,5].In light of previous works highlighting the perils of cross-validation using paired data [6,7], we recently investigated the effect of using drug-wise disjoint cross-validation in predicting drug-disease pairs, where none of the drugs in the training set appeared in the test set [8]. We showed that the prediction accuracy of the classifier drops dramatically under such cross-validation setting, suggesting that the existing approaches are prone to over-fitting due to the inherent relationships in the data.…”
mentioning
confidence: 99%
“…A potential DTI can be determined by the predicted class label. There are other possible solutions, and some recent reviews focused on the technical aspect of mathematical or statistical methods (12)(13)(14)(15)(16)(17). Regardless, prior knowledge of drugs, targets, and their interactions is required for all in silico method development.…”
Section: Introductionmentioning
confidence: 99%